Mechanisms of airway epithelial injury and abnormal repair in asthma and COPD - Raby, Katie Louise; Michaeloudes, Charalambos; Tonkin, James; Chung, Kian Fan; Bhavsar, Pankaj Kumar (Frontiers in Immunology, 2023)
The airway epithelium comprises of different cell types and acts as a physical barrier preventing pathogens, including inhaled particles and microbes, from entering the lungs.Goblet cells and submucosal glands produce mucus that traps pathogens, which are expelled from the respiratory tract by ciliated cells. Basal cells act as progenitor cells, differentiating into different epithelial cell types, to maintain homeostasis following injury. Adherens and tight junctions between cells maintain the epithelial barrier function and regulate the movement of molecules across it. In this review we discuss how abnormal epithelial structure and function, caused by chronic injury and abnormal repair, drives airway disease and specifically asthma and chronic obstructive pulmonary disease (COPD). In both diseases, inhaled allergens, pollutants and microbes disrupt junctional complexes and promote cell death, impairing the barrier function and leading to increased penetration of pathogens and a constant airway immune response. In asthma, the inflammatory response precipitates the epithelial injury and drives abnormal basal cell differentiation. This leads to reduced ciliated cells, goblet cell hyperplasia and increased epithelial mesenchymal transition, which contribute to impaired mucociliary clearance and airway remodelling. In COPD, chronic oxidative stress and inflammation trigger premature epithelial cell senescence, which contributes to loss of epithelial integrity and airway inflammation and remodelling. Increased numbers of basal cells showing deregulated differentiation, contributes to ciliary dysfunction and mucous hyperproduction in COPD airways. Defective antioxidant, antiviral and damage repair mechanisms, possibly due to genetic or epigenetic factors, may confer susceptibility to airway epithelial dysfunction in these diseases. The current evidence suggests that a constant cycle of injury and abnormal repair of the epithelium drives chronic airway inflammation and remodelling in asthma and COPD. Mechanistic understanding of injury susceptibility and damage response may lead to improved therapies for these diseases.